(untitled) (Al-Qamar, 2021)
This article is a study of the views of Muhammad Asad (1900-1992) regarding relationship between Muslim and western worlds. It makes a comparison of Asad’s view with some other distinguished scholars like Dr. Mahmood Ahmad Ghāzī, Marmaduke Pikthal etc. Quoting Asad and other scholars it concludes that West had been picking & choosing the beneficial particles from Muslim Civilization in the field of science and civilization. But in modern age when West has become in the position to give its science and technology to the Muslim world, it ruins political liberty of the Muslim world and destroy it spiritually and culturally. The West demanded from Muslim world to give up its cultural heritage and adopt western ideologies and ways of life with the claim that it is the only way of progress for the Muslims. Asad emphasizes on reconciliation between Muslim and Western worlds for better future of the human race. He says that despite their differences Muslims and the West may make friendly relation with each other. However he states that fundamental barrier between good relations of both the worlds is overwhelmed enmity and phobia of the West against Islam and Prophet of Islam. So it is mandatory for reconciliation and good relation amongst both the worlds that such irrational and unethical hostility, hatred and phobia of the West against Islam be deleted first. He says that in the prejudiced and hostile atmosphere they could never attain the goal of reconciliation. Asad expresses his distinctive opinion that West has the most powerful and dominant position in political, economic and technological spheres of life, hence it must take first step for the purpose of reconciliation between Islamic world and western worlds. He further emphasizes that for the better relation between both the worlds, the west should also give up the dual standard to deal with Muslim world. He also advises Muslims that they should explain and interpret Islam in such a way that may be easily understandable for the western world.